A Systemic Review of Resistance Mechanisms and Ongoing Clinical Trials in ALK-Rearranged Non-Small Cell Lung Cancer - Esfahani, Khashayar; Agulnik, Jason Scott; Cohen, Victor (Frontiers in Oncology, 2014)
The identification of oncogenic driver driver mutations in non-small cell lung cancer has led to a paradigm shift and the development of specific molecular treatments. Tumors harboring a rearranged EML4-ALK fusion oncogene are highly sensitive to therapy with ALK-targeted inhibitors. Crizotinib is the first approved treatment for advanced lung tumors containing this genetic abnormality. In this mini review, we discuss the existing data on crizotinib as well as ongoing trials involving this medication. A brief overview of the known resistance mechanisms to criztotinib will also be presented followed by a summary of the ongoing trials involving next-generation ALK inhibitors or other targeted therapies in patients with ALK+ NSCLC.